The Influence Of Rebranding And Brand Ambassador Nct Dream On Gen Z Purchasing Decisions On Tos Tos Products In Pontianak City - Dewi Citra Sekar Asih; Fita Kurniasari (UNIVED Press, 2024)
This study aims to find out the influence of rebranding and brand ambassador NCT Dream on the purchase decision of Gen Z on Tos Tos products in Pontianak City. This research uses associative methods with a quantitative approach. The sample used as many as 100 respondents who are Generation Z consumers and reside in Pontianak City. Sampling technique is purposive sampling. Research results show that the rebranding variable has a significant positive effect on the purchasing decision variable. As well, the brand ambassador variable has a significant positive influence on the purchasing decision variable.